Managing Chronicity in Unequal States Ethnographic perspectives on caring - Montesi, Laura; Calestani, Melania (Embodying Inequalities: Perspectives from Medical Anthropology, 2021)
By portraying the circumstances of people living with chronic conditions in radically different contexts, from Alzheimer's patients in the UK to homeless people with psychiatric disorders in India, Managing Chronicity in Unequal States offers glimpses of what dealing with medically complex conditions in stratified societies means. While in some places the state regulates and intrudes on the most intimate aspects of chronic living, in others it is utterly and criminally absent. Either way, it is a present/absent actor that deeply conditions people's opportunities and strategies of care. This book explores how individuals, groups and communities navigate uncertain and unequal healthcare systems, in which inherent moral judgements on human worth have long-lasting effects on people's wellbeing. This is key reading for anyone wishing to deconstruct the issues at stake when analysing how care and chronicity are entangled with multiple institutional, economic, and other circumstantial factors. How people access the available informal and formal resources as well as how they react to official diagnoses and decisions are important facets of the management of chronicity. In the arena of care, people with chronic conditions find themselves negotiating restrictions and handling issues of power and (inter)dependency in relationships of inequality and proximity. This is particularly relevant in current times, when care has given in to the lure of the market, and the possibility of living a long and fulfilling life has been drastically reduced, transformed into a 'reward' for the few who have been deemed worthy of it.